STUDIES ON THE IMMUNE RESPONSE TO A CHARACTERIZED ANTIGENIC DETERMINANT OF THE TOBACCO MOSAIC VIRUS PROTEIN - Spitler, Lynn (The Rockefeller University Press, 1970)
The following peptides have previously been shown to bind specifically with antibodies to TMVP: (a) An eicosapeptide representing residues 93–112 of TMVP and having the sequence Ileu-Ileu-Glu-Val-Glu-AspNH(2)-GluNH(2)-Ala-AspNH(2)-Pro-Thr-Thr-Ala-Glu-Thr-Leu-Asp-Ala-Thr-Arg. (b) Its C-terminal decapeptide. (c) Its C-terminal pentapeptide. (d) N-octanoyl-C-terminal-tripeptide. (e) (Lys)(4)-C-terminal-pentapeptide. (f) (Lys)(7) C-terminal-pentapeptide. The present communication deals with the investigation of several parameters of the immunological activity of the peptides. The results show that none of the peptides tested were immunogenic in guinea pigs, nor did they stimulate the incorporation of (14)C-thymidine by spleen cells derived from TMVP-primed animals. Results also showed that all of the peptides tested could elicit specific delayed and immediate skin reactions in TMVP-sensitized guinea pigs, and furthermore, that the peptides could specifically inhibit the migration of peritoneal exudate cells derived from these animals. The elicitation of delayed skin reactions and the ability to inhibit migration of peritoneal exudate cells were independent of carrier specificity.